Technoeconomic Modeling of Plant-Based Griffithsin Manufacturing - Alam, Aatif; Jiang, Linda; Kittleson, Gregory A.; Steadman, Kenneth D.; Nandi, Somen; Fuqua, Joshua L.; Palmer, Kenneth E.; Tusé, Daniel; McDonald, Karen A. (Frontiers in Bioengineering and Biotechnology, 2018)
Griffithsin is a marine algal lectin that exhibits broad-spectrum antiviral activity by binding oligomannose glycans on viral envelope glycoproteins, including those found in HIV-1, HSV-2, SARS, HCV and other enveloped viruses. An efficient, scalable and cost-effective manufacturing process for Griffithsin is essential for the adoption of this drug in human antiviral prophylaxis and therapy, particularly in cost-sensitive indications such as topical microbicides for HIV-1 prevention. The production of certain classes of recombinant biologics in plants can offer scalability, cost and environmental impact advantages over traditional biomanufacturing platforms. Previously, we showed the technical viability of producing recombinant Griffithsin in plants. In this study, we conducted a technoeconomic analysis (TEA) of plant-produced Griffithsin manufactured at commercial launch volumes for use in HIV microbicides. Data derived from multiple non-sequential manufacturing batches conducted at pilot scale and existing facility designs were used to build a technoeconomic model using SuperPro Designer modeling software. With an assumed commercial launch volume of 20 kg Griffithsin/year for 6.7 million doses of Griffithsin microbicide at 3 mg/dose, a transient vector expression yield of 0.52 g Griffithsin/kg leaf biomass, recovery efficiency of 70%, and purity of >99%, we calculated a manufacturing cost for the drug substance of $0.32/dose and estimated a bulk product cost of $0.38/dose assuming a 20% net fee for a contract manufacturing organization (CMO). This is the first report modeling the manufacturing economics of Griffithsin. The process analyzed is readily scalable and subject to efficiency improvements and could provide the needed market volumes of the lectin within an acceptable range of costs, even for cost-constrained products such as microbicides. The manufacturing process was also assessed for environmental, health and safety impact and found to have a highly favorable environmental output index with negligible risks to health and safety. The results of this study help validate the plant-based manufacturing platform and should assist in selecting preferred indications for Griffithsin as a novel drug.